2014
DOI: 10.1159/000358518
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Accuracy of Fetal Weight Estimation with a Focus on Preterm Birth at the Limit of Viability: A Systematic Literature Review

Abstract: Background: Fetal weight estimation (FWE) is an important factor for clinical management decisions, especially in imminent preterm birth at the limit of viability between 230/7 and 260/7 weeks of gestation. It is crucial to detect and eliminate factors that have a negative impact on the accuracy of FWE. Data Sources: In this systematic literature review, we investigated 14 factors that may influence the accuracy of FWE, in particular in preterm neonates born at the limit of viability. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 32 publications
4
20
1
4
Order By: Relevance
“…One factor not assessed by any of the studies and one systemic literature review involving 29 studies stated "No results were obtained on the impact of active labor" (13). In our study, active labor was not found to affect the accuracy of EFW.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…One factor not assessed by any of the studies and one systemic literature review involving 29 studies stated "No results were obtained on the impact of active labor" (13). In our study, active labor was not found to affect the accuracy of EFW.…”
Section: Discussioncontrasting
confidence: 54%
“…When we see the other studies mentioned previously in the literature review, the only factor that persistently affected EFW accuracy was the time interval between estimation and delivery i.e. 0-7 days vs. 8-14 days (13,17). But our study only included scans done within 7 days of delivery and the EFW was not affected among the scans done in this interval.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…No influence of BMI was described in the article by Hellebust et al [28] either. The accuracy of fetal weight estimation is not affected by BMI, which was put forward by other authors and also described in a systematic review of influencing factors by Huber et al [29,30,31,32]. …”
Section: Discussionmentioning
confidence: 74%
“…The accuracy of EFW at the limit of viability is susceptible to a variety of confounding factors [9] . We performed a retrospective analysis to determine the accuracy of EFW in the delivery room setting, and how inaccuracy may adversely affect neonatal morbidity and mortality by influencing clinical decisions.…”
Section: Methodsmentioning
confidence: 99%